Final safety and efficacy results from a 106 real‐world patients registry with an ascites‐mobilizing pump. (25th July 2022) - Stirnimann, Guido; Berg, Thomas; Spahr, Laurent; Zeuzem, Stefan; McPherson, Stuart; Lammert, Frank; Storni, Federico; Banz, Vanessa; Babatz, Jana; Vargas, Victor; Geier, Andreas; Engelmann, Cornelius; et al.
Abstract: Background and aims: Patients with cirrhotic refractory ascites ineligible for transjugular intrahepatic shunt (TIPSS) have limited treatment options apart from repeated large volume paracentesis. The alfapump® is an implantable device mobilizing ascites from the peritoneal cavity to the bladder, from where it can be excreted. The aim of this observational cohort study was to prospectively investigate safety and efficacy of the device in a real‐world cohort with cirrhotic refractory ascites and contraindications for TIPSS. Methods: A total of 106 patients received an implant at 12 European centres and were followed up for up to 24 months. Complications, device deficiencies, frequency of paracentesis, clinical status and survival were recorded prospectively. Results: Approximately half of the patients died on‐study, about a quarter was withdrawn because of serious adverse events leading to explant, a sixth were withdrawn because of liver transplant or recovery, and nine completed follow‐up. The most frequent causes of on‐study death and complication‐related explant were progression of liver disease and infection. The device reduced the requirement for large‐volume paracentesis significantly, with more than half of patients not having required any post‐implant. Survival benefits were not observed. Device‐related reinterventions were predominantly caused by device deficiencies. A post‐hoc comparison of the first 50 versus the last 50 patients enrolled revealed a decreased reintervention rate in the latter, mainly related to peritoneal catheter modifications. Conclusions: The device reduced paracentesis frequency in a real‐world setting. Technical complications were successfully decreased by optimization of management and device modification (NCT01532427).